1995
DOI: 10.1002/j.1460-2075.1995.tb07179.x
|View full text |Cite
|
Sign up to set email alerts
|

The ClpX heat-shock protein of Escherichia coli, the ATP-dependent substrate specificity component of the ClpP-ClpX protease, is a novel molecular chaperone.

Abstract: All major classes of protein chaperones, including DnaK (the Hsp70 eukaryotic equivalent) and GroEL (the Hsp60 eukaryotic equivalent) have been found in Escherichia coli. Molecular chaperones enhance the yields of correctly folded polypeptides by preventing aggregation and even by disaggregating certain protein aggregates. Previously, we identified the ClpX heat‐shock protein of E. coli because it enables the ClpP catalytic protease to degrade the bacteriophage lambda O replication protein. Here we report that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
208
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(214 citation statements)
references
References 53 publications
(44 reference statements)
6
208
0
Order By: Relevance
“…ClpX and related members of the Clp/Hsp100 protein family are AAA + ATPases (Neuwald et al ., 1999) which serve as specialized energy-dependent molecular chaperones to unfold specific target proteins, disassemble multimeric complexes and solubilize protein aggregates (Wickner et al ., 1994;Levchenko et al ., 1995;Wawrzynow et al ., 1995;Weber-Ban et al ., 1999;Zolkiewski, 1999;Kim et al ., 2000;Seonga et al ., 2000;Konieczny and Liberek, 2002). The minimal AAA + unit contains an ATPase domain with a mixed ab structure and a Cterminal domain that is largely a -helical, but most family members also contain additional structural domains (Schirmer et al ., 1996;Neuwald et al ., 1999;Bochtler et al ., 2000;Maurizi and Li, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ClpX and related members of the Clp/Hsp100 protein family are AAA + ATPases (Neuwald et al ., 1999) which serve as specialized energy-dependent molecular chaperones to unfold specific target proteins, disassemble multimeric complexes and solubilize protein aggregates (Wickner et al ., 1994;Levchenko et al ., 1995;Wawrzynow et al ., 1995;Weber-Ban et al ., 1999;Zolkiewski, 1999;Kim et al ., 2000;Seonga et al ., 2000;Konieczny and Liberek, 2002). The minimal AAA + unit contains an ATPase domain with a mixed ab structure and a Cterminal domain that is largely a -helical, but most family members also contain additional structural domains (Schirmer et al ., 1996;Neuwald et al ., 1999;Bochtler et al ., 2000;Maurizi and Li, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Different Clp/ Hsp100 family members generally have distinct substrate recognition preferences (Gottesman et al ., 1997a,b;Suzuki et al ., 1997). Well-characterized substrates of ClpX and ClpXP include the bacteriophage Mu transposase and proteins with ssrA degradation tags, both of which are recognized via C-terminal peptide sequences (Levchenko et al ., 1995;Wawrzynow et al ., 1995;Gottesman et al ., 1998;Gonciarz-Swiatek et al ., 1999;Kim et al ., 2000). Structural information is not available for ClpX, but several structures of the related HslU (ClpY) hexamer have been determined Song et al ., 2000;Sousa et al ., 2000;Wang, 2001;Wang et al ., 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The ClpP protease cylinder is capped at both ends by a large regulatory ATPase complex, ClpA\ClpX. Interestingly, it has been shown that the ATPases ClpA and ClpX direct the substrate specificity for the ClpP protease to different proteins [43][44][45]. In yeast, mutations in the different regulatory ATPases of the proteasomes result in different phenotypes [21] and alter the degradation of different substrates [46].…”
Section: Discussionmentioning
confidence: 99%
“…Degradation of complete mitochondrial translation products in an Afg3p-dependent manner indicates that proteolysis can occur post-translationally (Guélin et al 1996). Thus, Afg3p/Rca1p may also have a role in the removal of denatured or otherwise damaged proteins from the membrane can combine with ClpP subunits to form an ATP-dependent protease (Gottesman and Maurizi 1992;, can function independently as chaperones (Wickner et al 1994;Levchenko et al 1995;Wawrzynow et al 1995). Yeast mitochondrial Hsp78p, another member of the Clp-family, can partly substitute for mt-Hsp70 (Schmitt et al 1995) and/or stabilize mutant forms of the latter (Moczko et al 1995).…”
Section: Yme1pmentioning
confidence: 99%
“…Another is what the proposed chaperone function of the FtsH-subfamily proteins is in molecular terms. It must be noted in this respect that while 'assembly' or 'folding' are commonly used when referring to the proposed (second) function of these proteins, ClpA and ClpX promote disaggregation or monomerization (Wickner et al 1994;Levchenko et al 1995;Wawrzynow et al 1995).…”
Section: Yme1pmentioning
confidence: 99%